Utilization of the PPD application as a preventive effort for post partum blues - Fitriana Kurniasari Solikhah; Maria Diah Ciptaning Tyas (Peneliti Teknologi Teknik Indonesia, 2023)
The puerperium is a period when a mother will go through tiring days compared to the physical and psychological period of pregnancy which will further cause feelings of stress/depression. Mothers experiencing excessive stress have an impact on decreasing interest and interest in babies and the ability to care for their babies properly, not being enthusiastic about breastfeeding so that the health and development of the baby is not optimal. The novelty of this community service activity can provide education regarding the prevention of postpartum depression by using an application. This service activity was attended by posyandu cadres, couples of childbearing age (PUS), pregnant women and postpartum mothers. The purpose of this service activity is to increase public understanding of the prevention of postpartum depression, to be skilled at self-detection and its citizens about postpartum depression. The target of this activity is 40 people. The activity method is carried out twice by giving a pre test, lecture and followed by a post test by filling out a questionnaire. The evaluation was carried out with cadres by conducting interviews on their understanding of prevention of postpartum depression. The results achieved in this activity are that the community gains knowledge about postpartum depression.